The Role of Halal Certification in Protecting Indonesian and Thailand Producers and Consumers - Komariah, Kokom; Desi, Desi Fitriah; muty, yusran (At-Taradhi Jurnal Studi Ekonomi, 2024)
This study aims to analyzes the role halal certification protects producers and consumers in Indonesia and Thailand through document analysis from various sources. Halal certification is crucial for ensuring that the food and beverage industry adheres to Islamic sharia norms. A qualitative research approach was employed to gain an in-depth understanding of its purpose. Data collection comprised primary and secondary sources. Primary data included certification standards, evaluation reports, and policy documents from halal certification authorities, which directly address the role of halal certification in production. Secondary data was obtained from previous studies, scholarly articles, and relevant library materials. A thematic analysis was conducted to identify key themes and patterns related to the function of halal certification. The findings indicate that halal certification is vital for consumer protection, as it ensures compliance with sharia law and fosters customer loyalty. For producers, it enables adherence to strict quality standards, enhances competitiveness in domestic and international markets, and facilitates the development of industry regulations. This study highlights that halal certification is an effective tool for safeguarding consumer rights and promoting the growth of the halal market in both Thailand and Indonesia.                                                                       Penelitian ini bertujuan untuk mengkaji peran sertifikasi halal dalam melindungi produsen dan konsumen di Indonesia dan Thailand melalui analisis dokumen dari berbagai sumber. Sertifikasi halal sangat penting untuk memastikan bahwa industri makanan dan minuman mematuhi norma-norma syariah Islam. Pendekatan penelitian kualitatif digunakan untuk mendapatkan pemahaman mendalam tentang tujuannya. Pengumpulan data terdiri dari sumber primer dan sekunder. Data primer mencakup standar sertifikasi, laporan evaluasi, dan dokumen kebijakan dari otoritas sertifikasi halal, yang secara langsung membahas peran sertifikasi halal dalam produksi. Data sekunder diperoleh dari studi sebelumnya, artikel ilmiah, dan materi perpustakaan yang relevan. Analisis tematik dilakukan untuk mengidentifikasi tema dan pola kunci yang terkait dengan fungsi sertifikasi halal. Temuan menunjukkan bahwa sertifikasi halal sangat penting untuk perlindungan konsumen, karena memastikan kepatuhan terhadap hukum syariah dan membangun loyalitas pelanggan. Bagi produsen, sertifikasi halal memungkinkan kepatuhan terhadap standar kualitas yang ketat, meningkatkan daya saing di pasar domestik dan internasional, serta memfasilitasi pengembangan regulasi industri. Studi ini menyoroti bahwa sertifikasi halal merupakan alat yang efektif untuk melindungi hak-hak konsumen dan mendorong pertumbuhan pasar halal di Thailand dan Indonesia.